The Multiple Paths of Extraction, Dispossession, and Conflict in Mozambique: From Tete’s Coal Mines to Cabo Delgado’s LNG Projects - Blanes, Ruy Llera; Gonçalves, Euclides; Rodrigues, Ana Carolina (The Journal of Social Encounters, 2023)
When it comes to extractive processes, conflict, and peacebuilding, the case of Mozambique has recently taken center stage due to the emergence of an Islamic insurgency movement in the liquefied natural gas (LNG) project in its northern province of Cabo Delgado. This is but one part of a complex process of highly conflictual extractivist projects unfolding in the country. In this article, we argue that, beyond the specific case of LNG, there is a logic of continuity and accumulation regarding extraction-related grievances that, over the years, has generated community resentment in natural resource rich areas. Multiple accumulating forms of dispossession have accentuated community grievances in Tete’s coal mining areas and Cabo Delgado’s extractivist projects (LNG or otherwise), driving conflict associated with extractive industry projects. This paper is based on multiple rounds of field research conducted with residents and displaced people from extraction areas in the provinces of Tete and Cabo Delgado between 2012 and 2022. The analysis contributes to current debates on extractive politics, conflict, and peacebuilding.